Reconstructing Sharia Economic Dispute Resolution Based on Indonesian Muslim Society Culture - Nita Triana (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2017)
This paper describes the settlement of disputes in the field of Islamic economy based on Indonesian Muslim society culture. The research method used is Library research with normative juridical approach. In business, whether based on conventional or sharia, conflict or dispute sometimes happens and can not be avoided. The settlement of disputes in the Court, takes a long time, the cost is huge and the result is a win-lose, resulting in a sense of unfairness to either party. For that Sulh (peaceful) in resolving the dispute sharia economy becomes the choice of the sharia economic actors if there is a dispute between the parties. Sulh (peace) can be developed with various models, such as negotiation, mediation or arbitration. This dispute resolution model is more acceptable to the society, because philosophically the values of Sulh (peace) already exists intrinsically in the culture of Indonesian society which prioritizes deliberation and harmony in the life of society.